Evaluasi Sistem Informasi Manajemen Rumah Sakit Menggunakan Framework Human, Organization, And Technology-Fit (HOT-Fit) Model (Studi Pada RSI UNISMA Malang) - Fitri Dewi Lestari; Aditya Rachmadi; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Hospital Management Information System (SIMRS) is an information system used by RSI UNISMA Malang purposed to handle management process related to data and information of hospital services. This system is used to handle registration, nursing, pharmacy, medical records, laboratories, and finance. However, there are problems in implementing SIMRS which are able to decrease hospital service quality. This research purposes to evaluate SIMRS for knowing and describing system condition by using Human, Organization, and Technology (HOT-Fit) Model Framework. Data collecting was carried out using questionnaires methods by spreading the questionnaires to 100 respondents and also qualitative method by interviewing selected respondents. The research result showed that this information system has good quality since the organization supported its implementation. Based on the three aspects of HOT-Fit, aspect of technology gained the lowest value of all. There is conformity relationship among those three components, but there is still a nonconformity that needs improvement.